Analisis Fungsi Akreditasi Sekolah Dalam Peningkatan Produktivitas Sekolah - Zakia Nurhasanah; Hasyim Asyari; Sita Ratnaningsih (Universitas Pakuan, 2022)
SCHOOL ACCREDITATION FUNCTIONS IN INCREASING SCHOOL PRODUCTIVITY. This study aims to determine and analyze the function of school accreditation in increasing school productivity. This research uses qualitative research with descriptive method. This research was conducted at AQL Islamic School. The subject of this research is the Principal/Vice Principal,. The data collection technique of this research is observation, interviews and documentation. The results of this study indicate that school/madrasah test scores in the last 3 (three) years can be extracted from the average test scores, the AQL Islamic School has increased in the last three years as seen from the average test scores. This is due to the existence of tutoring apart from school, the school affiliates with several well-known tutors. Coupled with the free online tutoring. This is also supported by facilities and infrastructure, one of which is the school facilitating students with a kind of tablet to be able to access or look for things about lessons that have not been completed when studying in class. In addition, extracurricular activities at school also support students for their academic achievements. The existence of clubs such as science club, English club and many more. Then, judging from the public perception of the AQL Islamic School, this school is very good, because this AQL school has a fairly good Islamic base because of the holding of youth mosques. The academic achievements of the AQL Ialamic School itself have had many championships. One of them is in the National Science Competition championship.